Exploring the Influence of Students' Anxiety on English Language Learning in Online Integrated Instruction - Naila Luna Az Zahra; Sunarti Sunarti; Yeni Rahmawati (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This research explores the influence of online integrated learning on students’ anxiety within the English Language Education Program at Muhammadiyah University of East Kalimantan (UMKT). The study investigates the impact of online integrated learning in the English General Course on students' anxiety levels. It examines significant differences in anxiety levels between students actively using online platforms and those who do not. The sample consisted of 117 freshmen, with data collected via questionnaires assessing comfort with technology, perceptions of its effectiveness, and its impact on anxiety levels. Statistical analyses, including descriptive statistics, the One-Sample Kolmogorov-Smirnov Test, ANOVA, and Bonferroni multiple comparisons, were employed to provide a comprehensive understanding of the findings. Key results indicate a mean anxiety score of 41.55 and a mean achievement score of 78.21, reflecting moderate anxiety and relatively high academic performance. The One-Sample Kolmogorov-Smirnov Test confirmed the normal distribution of the data (p > 0.05), justifying the use of parametric methods. ANOVA results showed significant differences in anxiety levels and English scores based on online integrated learning (F = 166.159, p < 0.001). Bonferroni multiple comparisons revealed that lower anxiety was associated with higher English scores, with significant mean differences observed between low, medium, and high anxiety groups (p < 0.001). These findings suggest that online integrated learning significantly impacts students' anxiety levels, which in turn affects their academic performance. The study provides valuable insights for educators and policymakers on the importance of creating supportive and anxiety-reducing learning environments in technology-enhanced settings